PENGEMBANGAN LKPD BERBASIS KARAKTER KEARIFAN LOKAL PELAJARAN PPKn PADA KELAS IV SD - Iis Daniati Fatimah; Novialita Angga Wiratama (Jurnal Tunas Pendidikan, 2024)
This research aims to develop learning tools in the form of independent curriculum LKPD based on local wisdom for PPKn subjects in class IV elementary school. Development of local wisdom-based LKPD on regional cultural diversity material using development research (R&D) with 4D design to determine the validity of the research instruments used in the form of interview sheets and validation sheets. design validation, learning on aspects of graphic feasibility with an average score of 6.7, a percentage of 93% included in the "Very Feasible" category, while in the feasibility aspect of presentation the average score was 5, a percentage of 96% included in the "Very Feasible" category ”. Thus obtaining a total average score of 5.85, a percentage of 94.5% falls into the "Very Decent" category. In validating the learning material, scores were obtained for the appropriateness aspect of the content with an average score of 6.5, a percentage of 95% included in the "Very Eligible" category, while the average score for the language appropriateness aspect reached 5, a percentage of 87% included in the “Very Decent” category. So an overall average score of 4.8 was obtained, a percentage of 95% falling into the "Very Decent" category.